Implementation and evaluation on system generator of a cooperative system for 5G future systems - Melim, Joaquim Teixeira (2020)
With the arrival of 5G it is expected the proliferation of services in the different fields such as healthcare, utility applications, industrial automation, 4K streaming, that the former networks can not provide. Additionally, the total number of wireless communication devices will escalate in such a manner that the already scarce available frequency bandwidth won’t be enough to pack the intended objectives. Cisco’s Annual Internet Report from 2018 predicts that by 2023 there will be nearly 30 billion devices capable of wireless communication. Due to the exponential expiation of both services and devices, the challenges upon both network data capacity and efficient radio resourse use will be greater than ever, thus the urgency for solutions is grand. Both the capacity for wireless communications and spectral efficiency are related to cell size and its users proximity to the access point. Thus, shortening the distance between the transmitter and the receiver improves both aspects of the network. This concept is what motivates the implementation of heterogeneous networks, HetNets, that are composed of many different small-cells, SCs, overlaid across the same coexisting area of a conventional macro-cell, shortening the distance between the cell users and its access point transceivers, granting a better coverage and higher data rates. However, the HetNets potential does not come without any challenges, as these networks suffer considerably from communication interference between cells. Although some interference management algorithms that allow coexistence between cells have been proposed in recent years, most of them were evaluated by software simulations and not implemented in real-time platforms. Therefore, this master thesis aims to give the first step on the implementation and evaluation of an interference mitigation technique in hardware. Specifically, it is assumed a downlink scenario composed by a macro-cell base station, a macro-cell primary user and a small cell user, with the aim of implementing an algorithm that eliminates the downlink interference that the base station may cause to the secondary users. The study was carried out using the System Generator DSP tool, which is a tool that generates code for hardware from schematics created in it. This tool also offers a wide range of blocks that help the creation, and fundamentally, the simulation and study of the system to be implemented, before being translated into hardware. The results obtained in this work are a faithful representation of the behavior of the implemented system, which can be used for a future application for FPGA.